Europe in teaching practice – national and international experiences - Horváth, Ágnes (Sens public)

(untitled) (Département des littératures de langue française, 2009)
During the past six years I was fortunate to teach European Studies to Hungarian and foreign students within teacher training and further education as well. The lecture tries to summarize the most important features and approaches used in teacher training programmes, special programmes for in-service teachers and international seminars. The key questions of the approach are: How to define Europe as historical, geographical and cultural phenomena; How to motivate participants to get acquainted with European issues; How to promote European identity and citizenship; How to balance national and international features of European values, movements and relations; How to develop critical thinking and intercultural communication within European studies? Conclusion: teaching Europe would be much more efficient if we used concrete and up to date information to obtain personal interest and individual participation in different debates, projects, presentations and later on independent actions as well.